Reshaping social democracy: Labour and the SPD in the New Century - Haseler, Stephen (European Research Forum at London Metropolian Univ., 2004)
Is Tony Blair still a social democrat or did New Labour break with the history and traditions of social democracy? What is the direction of Gerhard Schroder and his governing party SPD in Germany? Do the two most important European left of center governments believe in the same kind of reform process or do they represent different approaches, not only regarding the Iraq war? This collection of essays provides up to date analyses of ideological change, governmental politics and structural affiliations of two protagonists of European social democracy: the British Labour Party and the German SPD. The authors of the respective chapters set their examinations in an historical and national perspective and hence allow readers to draw their own conclusions of the recent developments of the SPD and the British Labour Party. Consisting of eleven chapters by twelve authors this volume brings together some of the most recognised academic experts on social democracy and the labour movement from Britain and Germany.